(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2010)
Keywords: brain biopsy; frame-based biopsy; stereotactic DOI: 10.3329/jcmcta.v20i2.5622 Journal of Chittagong Medical College Teachers’ Association 2009: 20(2):24-28